2017
DOI: 10.1136/bmjopen-2016-013366
|View full text |Cite
|
Sign up to set email alerts
|

Treatment trends for retinopathy of prematurity in the UK: active surveillance study of infants at risk

Abstract: ObjectivesTo estimate the incidence of severe retinopathy of prematurity (ROP) requiring treatment and describe current treatment patterns in the UK.DesignNationwide population-based case ascertainment study via the British Ophthalmic Surveillance Unit and a national collaborative ROP special interest group. Practitioners completed a standardised case report form (CRF).SettingAll paediatric ophthalmologists providing screening and/or treatment for retinopathy in the UK were invited to take part.ParticipantsAny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
56
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 27 publications
5
56
1
4
Order By: Relevance
“…The recent British Ophthalmic Surveillance Unit study indicated that nearly 30% of babies treated have Type 2 disease. 1 Potentially unnecessary laser treatment for Type 2 ROP, with all the risks it entails, was prevented in most cases by telemedicine in this study.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…The recent British Ophthalmic Surveillance Unit study indicated that nearly 30% of babies treated have Type 2 disease. 1 Potentially unnecessary laser treatment for Type 2 ROP, with all the risks it entails, was prevented in most cases by telemedicine in this study.…”
mentioning
confidence: 68%
“…(Type 1) ROP and require treatment. 1 Recognition of progression to Type 1 ROP and timely laser treatment is essential to prevent permanent visual loss, which accounts for 3% of childhood visual loss in the UK. 2 Current issues with ophthalmologist delivered screening in the UK include recruitment difficulties, inexperience of screeners and the lack of a certified programme of continued medical education.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…При сравнении результатов ультразвукового офтальмосканирования (высота и протяженность вала ЭРП) выявлены аналогичные для данных цифровой морфо- метрии зависимости: существенное отличие для групп 1 и 2 (F = 168,1 и F = 61,5 при р < 0,01) и отсутствие различий для групп 2 и 3 (F = 1,3 и F = 0,5 для высоты и протяженности вала ЭРП, соответственно, при р < 0,01) (рис. 4,5).…”
Section: пациенты и методыunclassified
“…Однако в ряде случаев в специализированных офтальмологических центрах при первичном поступлении продолжают встречаться впервые выявленные стадии экссудативно-тракционной отслойки сетчатки (ОС) задней агрессивной РН [3,4].…”
unclassified